The Anti-Cancer Effect of Linusorb B3 from Flaxseed Oil through the Promotion of Apoptosis, Inhibition of Actin Polymerization, and Suppression of Src Activity in Glioblastoma Cells - Sung, Nak Yoon (Molecules, 2020)
Linusorbs (LOs) are natural peptides found in flaxseed oil that exert various biological activities. Of LOs, LOB3 ([1–9-NαC]-linusorb B3) was reported to have antioxidative and anti-inflammatory activities; however, its anti-cancer activity has been poorly understood. Therefore, this study investigated the anti-cancer effect of LOB3 and its underlying mechanism in glioblastoma cells. LOB3 induced apoptosis and suppressed the proliferation of C6 cells by inhibiting the expression of anti-apoptotic genes, B cell lymphoma 2 (Bcl-2) and p53, as well as promoting the activation of pro-apoptotic caspases, caspase-3 and -9. LOB3 also retarded the migration of C6 cells, which was achieved by suppressing the formation of the actin cytoskeleton critical for the progression, invasion, and metastasis of cancer. Moreover, LOB3 inhibited the activation of the proto-oncogene, Src, and the downstream effector, signal transducer and activator of transcription 3 (STAT3), in C6 cells. Taken together, these results suggest that LOB3 plays an anti-cancer role by inducing apoptosis and inhibiting the migration of C6 cells through the regulation of apoptosis-related molecules, actin polymerization, and proto-oncogenes.